МӘҢГИЛЕСТИРИЛИЎИ ТИЙИС МУҚАДДЕС МӘДЕНИЙ МИЙРАСЛАР (тарийхы, ҳәзирги ҳалаты, келешек тәғдири мәселелери) - Алламбергенов, К.; Эгамкулова, Г.М. (FAN va JAMIYAT, 2021)
The article deals with some valuable recommendations and necessary solutious of karakalpak bakshis’ (folk songs), art of guttural singing, national heritages, origin of this art, traditions which continious from long times, present conditions, musical instruments and oratory art, school of tutors.